Dynamics of the atmosphere : a course in theoretical meteorology - Zdunkowski, Wilford, 1929- (Cambridge University Press, 2003)
Complete with numerous exercise sets and solutions, Dynamics of the Atmosphere is written for advanced undergraduate and graduate students of meteorology and atmospheric science. The book consists of two parts, the first presenting the mathematical tools needed for a thorough understanding of dynamic atmospheric phenomena discussed in the second part.